Pharmacological Modulation of Anti-Tumor Immunity Induced by Oncolytic Viruses - Forbes, Nicole E.; Krishnan, Ramya; Diallo, Jean-Simon (Frontiers in Oncology, 2014)
Oncolytic viruses kill cancer cells by direct lysis but also generate a significant anti-tumor immune response that allows for prolonged cancer control and in some cases cures. How to best stimulate this effect is a subject of intense investigation in the oncolytic virus field. While pharmacological manipulation of the cellular innate antiviral immune response has been shown by several groups to improve viral oncolysis and spread, it is increasingly clear that pharmacological agents can also impact the anti-tumor immune response generated by oncolytic viruses and related tumor vaccination strategies. This review covers recent progress in using pharmacological agents to improve the activity of oncolytic viruses and their ability to generate robust anti-tumor immune responses.